Performance Evaluation of Multi-Hop LoRaWAN - Md. Rakibul Islam; Md. Bokhtiar-Al-Zami; Biswajit Paul; Rajesh Palit; Jean-Charles Gregoire; Salekul Islam (IEEE Access, 2023)
Although LoRa (radio) technology offers customization of different physical layer transmission parameters such as bandwidth, spreading factor (SF), transmission power, and coding rate to obtain the desired data rate and coverage, the currently preferred single-hop transmission mode cannot simultaneously achieve both. The LoRaWAN community is therefore focusing on multi-hop networks to increase network longevity while extending coverage. In this paper, a detailed mathematical model for a multi-hop network that modifies the Distance Ring Exponential Stations Generator (DRESG) framework is presented. The relay operation is carried out through intermediate gateways, and a distance-based adaptive transmission configuration approach is used. On the basis of the performance metrics, i.e., packet delivery ratio (PDR) and energy usage of end nodes, we compare and contrast the performance characteristics of several routing schemes, including single-hop (SH), next-ring-hop (NRH), and variable-hop (VH) routing. The research covers some core issues, including interference, environmental conditions, and transceiver power constraints, and sets the stage for evaluating various multi-hop LoRa solutions as well as optimizing several implementation factors.